Sustainable consumption and the UK's leading clothing retailers. (8th November 2010) - Jones, Peter; Comfort, Daphne; Bown, Robin; Hillier, David
This paper offers an exploratory case study of how the UK's leading clothing retailers are communicating sustainable consumption agendas to their customers within stores. A discussion of the growing awareness of the role that retailers can play in promoting sustainable consumption is followed by a literature review of sustainable consumption and an outline of the retail clothing sector within the UK. A simple visual observation and recording survey revealed that while the UK's top ten clothing retailers were providing customers with limited information on sustainable consumption, the dominant thrust of marketing communication within stores was designed to encourage consumption. The paper offers some reflections on the role of retailers and customers in driving sustainable consumption and concludes that the UK's leading clothing retailers' definitions of, and engagement with, sustainable consumption are driven by commercial imperatives as by their commitment to sustainability.